Plasma modification of metal oxides and textiles: tailoring surface properties for improved gas sensor and protective clothing applications - Hiyoto, Kimberly A. M., author; Fisher, Ellen R., advisor; Menoni, Carmen S., committee member; Rappe, Anthony K., committee member; von Fischer, Joseph C., committee member (Colorado State University. Libraries, 2021)
This dissertation focuses on utilizing inductively coupled plasma processing to modify various materials for applications in gas sensing and protective clothing. By relating changes in the plasma gas-phase during treatment, resulting material characteristics, and application-based performance, insights into how these materials work can be gained. Ultimately, this knowledge allows for a targeted approach to optimizing the material's surface properties for a specific behavior. The first part of this work concentrates on the plasma modification of semiconducting metal oxides (SMO) to create gas sensors that are more responsive to a target gas at lower operating temperatures. First, SnO2 nanoparticles (NP) supported by a traditional substrate (ZrO2 wafer) were treated with a CO or CO2 plasma as a function of applied plasma power (P). X-ray photoelectron spectroscopy (XPS) analysis of the NP after plasma exposure demonstrates that the CO plasma deposits an amorphous carbon film, whereas the CO2 plasma results in the etching of the SnO2 lattice. Optical emission spectroscopy (OES) studies were used to identify key excited-state species in the plasma gas-phase to explain the depositing and etching nature of these two systems. Gas sensing performance studies demonstrate that the deposition of a film on the SnO2 blocked analyte-sensor interactions, resulting in a negative effect on the response of the sensor. The CO2 plasma treated sensors, however, displayed an increased response to benzene and CO at lower operating temperatures when compared to the untreated (UT) material. The adaptation of the SnO2 sensor and plasma treatments to be compatible with a paper-based sensor (PGS) provided positive indicators for future studies. Indeed, an Ar/O2 plasma was used to treat SnO2 NP PGS at P = 15 – 60 W. Similar to the CO2 plasma, this system has also been shown to etch the SnO2 lattice resulting in improved device performance. The PGS treated at 15 and 60 W showed an increased response to ethanol and CO at operating temperatures ≤50 °C. These studies indicate that the selectivity of the sensor can be tuned with plasma P. Additionally, these sensors showed some response and recovery behavior to ethanol, indicating that these devices are robust enough to be used multiple times. Preliminary work expanding the SMO used to make these PGS is also included to demonstrate the applicability of this device fabrication and plasma modification methods for other materials and SMO morphologies. These gas sensor studies highlight the importance of understanding the relationship between surface properties and device performance. By obtaining a better understanding of the gas detection process, a targeted approach to fabricating improved gas sensors can be established. The final section of this work examines the effect of fabric hydrophobicity on NP attachment and resuspension. These studies employed C3F8 and H2O(v) plasmas to treat four common lab coat materials. XPS and water contact angle goniometry confirm that the C3F8 plasma treatment increases the hydrophobicity of the fabrics and the H2O(v) plasma increases the wettability of most materials. Hydrophobic recovery studies of the H2O(v) treated samples suggest that there are minimal aging effects on the Tyvek® and 100% cotton fabrics, but further work is needed to optimize the plasma parameters for the 80/20 polyester/cotton and 100% polypropylene samples. The attachment and release behavior of Al2O3 NP, carbon black, and carbon nanotubes with the UT and treated materials are also discussed. Ideally, personal protective clothing should either repel (preventing initial NP attachment and fabric contamination) or hold on to (limiting the potential for secondary exposure from contaminated clothes) NP. In general, it is thought that the tightness of the fabric weave is the only factor that influences NP attachment and resuspension. Scanning electron microscopy images of the contaminated and shaken fabrics reveal that the surface chemistry of the material cannot be excluded as the attachment and release of the nanomaterials differed between the C3F8, H2O(v), and UT fabrics. Through these studies, fabric characteristics that influence the interaction with nanomaterials are explored and can be used to inform better safety recommendations when working with these materials.